1936
DOI: 10.1128/jb.32.4.361-373.1936
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Energy as a Lethal Agent for Yeast and Bacteria

Abstract: Crystalline quartz has a certain characteristic which is fundamental to the experiments which we have performed. It is piezo active. Wood and Loomis have described an apparatus which we have utilized with certain modifications and which gives rise to the piezo effect. With this apparatus we have conducted certain experiments dealing with the killing effect of this source of energy upon bacteria and yeasts.' Wood and Loomis (1927) have demonstrated that ultrasonic radiation can disrupt certain higher forms of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

1939
1939
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Although the protective effect of whole milk observed by Beckwith & Weaver (1936) had been confirmed, it was remarkable that the reconstituted skim mill< was not equally effective, since those workers had ascribed the milk effect to the casein content, and the 8% concentration had been used because it was presumed that its protein content would have been roughly equal to that in fresh milk, i.e. about 40/,, the other 4O/, being lactose and salts.…”
Section: The Treatment Of Various Bacteriamentioning
confidence: 99%
See 3 more Smart Citations
“…Although the protective effect of whole milk observed by Beckwith & Weaver (1936) had been confirmed, it was remarkable that the reconstituted skim mill< was not equally effective, since those workers had ascribed the milk effect to the casein content, and the 8% concentration had been used because it was presumed that its protein content would have been roughly equal to that in fresh milk, i.e. about 40/,, the other 4O/, being lactose and salts.…”
Section: The Treatment Of Various Bacteriamentioning
confidence: 99%
“…The bacteria already mentioned were exposed to ultrasonic waves a t one or both of the frequencies available. Most of them were treated in three different liquids, as it was known (Beckwith & Weaver, 1936) that the suspension medium could exert a marked effect on the destructive effect produced. The fluids were: nutrient broth, an So/, (w/v) solution of dried skim milk, and glass-distilled water.…”
Section: The Treatment Of Various Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…These phenomena have been investigated using the Cavi-Endo ultrasonic endodontic unit by Ahmad et al (2). Studies in other disciplines have shown that these phenomena could cause cell disruption (3,4).…”
mentioning
confidence: 99%